The Role of Visual Merchandise in Changing the Purchase Decision of Shoppers within Retail Stores in Jordan - Hashem, Tareq Nael (Jurnal The Messenger, 2019)
Attracting new customers means to take novel measures by stores. Nowadays, stores are designed in order to guarantee a fast purchase decision by customers. The current study seeks to understand the role of visual merchandise on decision of purchasers to buy a certain item. The variables taken into considerations are color, landscaping, texture, communication and D ©cor. Sample of study consisted of 1000 individuals from commercial complexes and malls in Jordan. Through the quantitative approach depending on self-administered questionnaire, results of study indicated that color and landscaping are the most influential factors that may influence the purchase decision of individuals, followed by texture, communications, and d ©cor. The study therefore recommends that store managers should pay more attention to the details of the stores in a way that matches the taste of people who attend these stores.